Ceramic membrane bioreactor for wastewater reclamation - Teo, Wei Liang (2017)
Membrane bioreactor is gaining popularity in wastewater treatment due to some advantages over conventional wastewater treatment plant. However, like all membrane technology, membrane fouling remained inevitable. Chemical cleaning using NaClO has been widely used to remediate membrane fouling. However, many negative effects were found which posed some concerns. Ozone, another cleaning agent has shown to give promising results. The objective of this study was to investigate the effects of ozone on ceramic membrane in regard to fouling while comparing the results with NaClO. It was found that ozone was more effective than NaClO as a cleaning agent.